2017
DOI: 10.1093/gji/ggx155
|View full text |Cite
|
Sign up to set email alerts
|

Retrieving impulse response function amplitudes from the ambient seismic field

Abstract: Seismic interferometry is now widely used to retrieve the impulse response function of the Earth between two distant seismometers. The phase information has been the focus of most passive imaging studies, as conventional seismic tomography uses traveltime measurements. The amplitude information, however, is harder to interpret because it strongly depends on the distribution of ambient seismic field sources and on the multitude of processing methods. Our study focuses on the latter by comparing the amplitudes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…In such virtual source reconstructions, the authors are careful to only consider station‐station paths over a narrow range of azimuths and are careful to stack all NCFs over a consistent time period, thus mitigating potential biases from inhomogeneous noise source distributions. Viens et al () also demonstrate that while temporal and azimuthal variations in noise source may contribute to variability in NCF amplitudes, such errors are small compared to the large effect of sedimentary basin amplifications they observe, indicating that direct observation can still be useful in some contexts.…”
Section: Introductionmentioning
confidence: 99%
“…In such virtual source reconstructions, the authors are careful to only consider station‐station paths over a narrow range of azimuths and are careful to stack all NCFs over a consistent time period, thus mitigating potential biases from inhomogeneous noise source distributions. Viens et al () also demonstrate that while temporal and azimuthal variations in noise source may contribute to variability in NCF amplitudes, such errors are small compared to the large effect of sedimentary basin amplifications they observe, indicating that direct observation can still be useful in some contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Particular attention has been paid to understand the effect that the inhomogeneous distribution of noise sources would have on the coherence or cross‐correlation measured between stations, with the goal of determining whether measurements can be reliably used for the study of seismic velocities or attenuation (e.g., Cupillard & Capdeville, ; Harmon et al, ; Lawrence & Prieto, ; Tsai, , ; Weaver, ; Yang & Ritzwoller, ), with additional studies exploring the extent to which signal preprocessing can reduce the effect of inhomogeneous noise sources (e.g., Bensen et al, ; Viens et al, ). Some of these velocity or attenuation measurements require a great amount of precision and stability over time (Froment et al, ), such as for the observation of material velocity changes; velocity variations on a daily or monthly time scale may be as small as a couple percent but have been shown to yield valuable information regarding temperature or pore pressure changes (i.e., Brenguier et al, ; Lecocq et al, ; Taira & Brenguier, ).…”
Section: Introductionmentioning
confidence: 99%
“…Using data from the shallow‐depth mine collapse event, we have more thoroughly demonstrated the capability to retrieve IRFs from an ambient seismic field absent a correction for the occurrence depth or source mechanism. Viens et al () also demonstrated that the sensitivities of retrieved amplitudes to seasonal variations are relatively small throughout the year for the deconvolution method. These findings correspond with the results of this study.…”
Section: Resultsmentioning
confidence: 99%
“…Geophysical Research Letters 10.1002/2017GL075532 absent a correction for the occurrence depth or source mechanism. Viens et al (2017) also demonstrated that the sensitivities of retrieved amplitudes to seasonal variations are relatively small throughout the year for the deconvolution method. These findings correspond with the results of this study.…”
Section: 1002/2017gl075532mentioning
confidence: 87%